2007
DOI: 10.1021/jp068640x
|View full text |Cite
|
Sign up to set email alerts
|

Toluene Combustion:  Reaction Paths, Thermochemical Properties, and Kinetic Analysis for the Methylphenyl Radical + O2 Reaction

Abstract: Aromatic compounds such as toluene and xylene are major components of many fuels. Accurate kinetic mechanisms for the combustion of toluene are, however, incomplete, as they do not accurately model experimental results such as strain rates and ignition times and consistently underpredict conversion. Current kinetic mechanisms for toluene combustion neglect the reactions of the methylphenyl radicals, and we believe that this is responsible, in part, for the shortcomings of these models. We also demonstrate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 63 publications
(52 reference statements)
6
94
0
Order By: Relevance
“…Among the important pathways, the addition of molecular oxygen on methylphenyl radicals has been investigated in great detail by da Silva et al [36]. They report that the dominant reaction products are the cresoxy and methyloxepinoxy radicals (Fig.…”
Section: Attack On the Aromatic Ringmentioning
confidence: 99%
“…Among the important pathways, the addition of molecular oxygen on methylphenyl radicals has been investigated in great detail by da Silva et al [36]. They report that the dominant reaction products are the cresoxy and methyloxepinoxy radicals (Fig.…”
Section: Attack On the Aromatic Ringmentioning
confidence: 99%
“…15 Despite the difference in bond dissociation energies, abstraction reactions by reactive free radicals are expected to provide significant yields of methylphenyl radicals; for instance at 1000 K the product branching ratio for methylphenyl and benzyl radicals by OH abstraction reactions is close to 1 : 3, increasing to 1 : 2 at 2000 K. 16 The toluene C-CH 3 bond scission, yielding the phenyl radical, is also significant during thermal decomposition: 20% at 1200 K, and 40% at 1500 K. 17 Likewise, decomposition of poly-methyl substituted benzenes, such as ortho-xylene, can produce methylphenyl radicals. 18,19 Isomerisation of the methylphenyl radical to benzyl radical is generally competitive under high-temperature combustion conditions, however lifetimes of methylphenyl species near autoignition temperatures (B1000 K) are such as to permit bimolecular reactions with O 2 . 19,20 Despite their plausible contribution in combustion environments, the methylphenyl + O 2 reaction has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…One computational study has suggested that the 2-methylphenyl + O 2 reaction is substantially different from that of the unsubstituted phenyl radicals, in which formation of 2-quinone methide + OH is thought to compete (via a process shown in Scheme 1) with phenylperoxyltype isomerisation. 18 Experimental investigation of the methylphenyl + O 2 system can further the current understanding of toluene oxidation. However, identification and characterisation of reaction intermediates and products remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In daytime, the reaction of aromatic hydrocarbons with hydroxyl radicals is the major atmospheric loss process [14][15][16]. Several previous experimental [17][18][19] and theoretical [20][21][22][23][24][25][26] studies have unraveled the elementary reactions involved in aromatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that in the presence of OH radical the main reaction path is OH addition to the aromatic ring to form a xylene-OH adduct (consuming $90% of OH radicals) with Habstraction from one methyl group to form a methylbenzyl radical (consuming $10% of OH radicals) being the minor route [18,[31][32][33][34]. In addition, theoretical investigations have mainly focused on OH-addition to xylene and the fate of xylene-OH adducts and intermediates [15,26,31,[34][35][36], whereas the H-abstraction mechanism for p-xylene oxidation following the initial OH attack and subsequent products have only been studied experimentally [22,25,37,38].…”
Section: Introductionmentioning
confidence: 99%